Criatividade e desenvolvimento de competências gerenciais em empresas de base tecnológica. - Alves Filho, Luiz da Costa (2016)
This study aimed to understand the perception of managers of technology-based companies (TBCs) about creativity and its implications for the development of managerial competencies. To this end, the following specific objectives have been defined: a) characterize the meaning of creativity in the perception of the TBCs managers; b) identify the role of creativity in the context of professional performance of TBCs managers; c) identify managerial competencies of TBCs linked to creativity and; d) verify the implications of creative thinking and technological environment in the development of managerial competencies in TBCs. The Literature review was structured by creativity, which involves the creative environment, creative work and creative management; managerial competencies, technology-based companies and their characterization. The research qualifies as a qualitative approach and was held with managers of companies of technological basis, participants of technology incubator of Campina Grande-PB, in a total of 9 (nine) respondents linked to 8 companies. The interviews were transcribed, categorized and interpreted through content analysis. The categorization of the data process enabled the delimitation of the following dimensions: creativity in the perception of TBCs managers, the role of creativity in the context of managerial TBCs, the link between managerial competencies and creativity in TBCs and implications of creative thinking and technological environment in the development of managerial compettencies. The survey results revealed that managers perceive a significant link between creativity and innovation, being nearly inseparable. In this perspective, creative actions are associated with both the product development as the changes in organizational processes. The findings still indicate some factors that foster creativity through internal and external stimulus and that demand of managers to have an open mind to obtain insights and being able to generate ideas and promote company creative solutions. In addition, the results point to creativity as essential in the context of managerial action, as it allows the managers to develop innovative actions to enhance the company's competitiveness, facilitating both the interpersonal relationship, conflict management and expectations among stakeholders as to its ability to take advantage of new business opportunities and open up new horizons for the company. All these aspects associated with managerial resilience that the managers develop through the dynamic environment in which its companies operate and require of their managers the notion of constant learning, essential to develop managerial competencies aligned to creativity to cope with the hardships inherent in the tech industry. Some creative experiments were also mentioned carried out within the participating companies, which enabled the practical visualization of actions considered simple, but that can be the difference wich the market and customers were waiting to see value in the company. Besides, it is believed that this work can to broaden the discussion about a relatively new phenomenon in the study of management - creativity - and their implications in dynamic work environments. The reflections still suggest raising the optimisation of human capital in these contexts, which can be result of a generation that prioritizes flexibility, recognition and quality of life.